Fuzzy Adaptive Sliding Mode Control of Large Erecting Mechanism - Li Liang; Xie Jian; Huang Jian Zhao (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Sincethe large erecting mechanism has nonlinearities, parameter uncertainties andexternal disturbance, it is difficult to realize a model-based sliding modecontrol design. So a fuzzy adaptive sliding mode control scheme which combinedfuzzy control with sliding mode control is proposed to achieve nonlinearcontrol of the erecting mechanism. This control scheme is mainly use the fuzzysystem to approximate the equivalent control of the sliding mode controllerwithout knowing the system dynamic model. And it also releases thetrial-and-error work of establishing the fuzzy inference rules. The update lawsfor the fuzzy tuning parameters and the switch control parameter are derivedbased on the Lyapunov stability analysis. The simulation results show that comparedto the PID control and conventional sliding mode control, the fuzzy adaptivesliding mode control has nicer robustness and more accurate tracking ability,and the stability of the erecting process has improved. DOI: http://dx.doi.org/10.11591/telkomnika.v11i12.3818